Działania Europejskiego Mechanizmu Stabilizacji Finansowej EFSM oraz Europejskiego Funduszu Stabilizacji Finansowej EFSF — stan na 1 grudnia 2011 roku - Mundry, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
As a result of the crisis in Greece and the volatile situation on financial markets, the EU decided to implement a European Stabilisation Mechanism. Detailed and in depth article examines the operation of The European Financial Stabilisation Mechanism EFSM and The European Financial Stability Facility EFSF.The EFSM, the Commission may borrow a total of 60 billion euros in the financial markets on behalf of the European Union, as part of an unconditional guarantee ofthe EU budget. The European Financial Stability Facility EFSF was created by the euro area Member States following the decisions taken on 9 May 2010 within the framework of the Ecofin Council. It may issue bonds to total 440 billion euros. These bonds are guaranteed by the EAMS Euro Area Member States.
Keywords: Europejski Mechanizm Stabilizacji Finansowej (EFSM); Europejski Fundusz Stabilizacji Finansowej (EFSF)